A Family Life and Sex Education Needs Assessment - West, Lloyd W.; Woods, Merl (Canadian Journal of Counselling and Psychotherapy, 2011)
A change in counselling focus from psychotherapy to psychoeducation has left many counsellors illprepared to develop and evaluate programs designed to meet the specific needs of their clients. This article illustrates how these tasks may be facilitated by the use of needs assessment technology. Needs are defined as measurable discrepancies between ideal situations and actual situations. Those needs for which the school has been assigned significant responsibility are designated as curricular needs. The article reports on the findings of a family life and sex education needs assessment conducted in the Calgary public school system. The implications of the findings of this study are discussed but the reader is cautioned not to over-generalize to other settings.